Contributors’ Biography Notes - -, - (Journal of the Canadian Association for Curriculum Studies, 2018)
The contributor biography notes for the JCACS Special Issue, Summer 2018: The Arts in Curriculum: Aesthetics, Embodiment and Well-Being.